A new statistical technique for analysis of repeated responses - SINGH, RAJENDRA; KUMAR, DINESH; RAWAL, C V S (The Indian Journal of Animal Sciences, 2013)
An oestrous cycle cllrve of pH values of vaginal mucus of sheep has been established. This model explained about 72.61 to 88.72 % variability of pH data barring few exceptions. The pH values during first and last 3 days were always more than 8.00. A procedure has been .laid down to identify the stage of oestrous cycle of an ewe. An analysis method has been proposed to analyze the missing data when they form a curve in association with some other continuous variable. As the length of oestrous cycle became more than 18 days, the declining (B1) and rising (B2) extremes of the curve increased substantially along with days of minima in the curve.